EDUKASI PANGAN DAN JAJANAN YANG AMAN SEHAT SERTA BERMUTU DI SMA NEGERI 20 BATAM : - Amalia, Eva; Afriani, Miratia; Gunawan, Agung, Arif; Puspita Rini, Rosie Oktavia, (PUSLITABMAS-Politeknik Pariwisata Batamc, 2024)
This community service initiative is designed to provide an alternative educational platform targeting both educators and students. Furthermore, it seeks to engage the participation of students' parents and committees in supporting school food safety programs. Concurrently, educators are equipped with the skills to enhance the management of school canteens, ensuring the provision of snacks that meet stringent safety, quality, and nutritional standards. The primary objective is to cultivate awareness among all members of the school community regarding the paramount importance of selecting snacks that are not only safe but also of high quality and nutritional value. It is anticipated that this heightened awareness will empower the community to make judicious choices in their food consumption. The methodology employed in this community service initiative includes the dissemination of learning materials and references through structured presentations and interactive sessions, incorporating a question-and-answer format. Participants undergo a comprehensive learning process, acquiring knowledge and practical skills through demonstrative sessions that are subsequently applied. Through the evaluation of program implementation and outcomes, factors supporting or hindering the success of this community service initiative can be discerned. The socialization process places a particular emphasis on elucidating the potential hazards associated with the misuse of substances in food, such as rhodamine B, methanyl yellow, formalin, and borax. Participants are not only informed about these dangers but are also provided with guidance on effectively educating and guiding students towards the consumption of healthful snacks. The initiative additionally aspires to motivate educators to prioritize the psychological well-being of their students, with the ultimate goal of fostering independence within the school community concerning food safety.